Analysis of reactor experiments to study the transfer processes of generated tritium in lithium CPS (capillary-porous system); International Journal of Hydrogen Energy; Vol. 47, iss. 11 - Askerbekov S. K. Saulet Kanybekuly; Kenzhina I. Е. Inesh; Kulsartov T. V. Timur; Chikhray E. V. Evgeny Vasiljevich; Tazhibaeva I. L. Irina Lashkarovna; Ponkratov Yu. V. Yury Valentinovich; Gordienko Yu. N. Yury Nikolaevich; Zaurbekova Zh. A. Zhanna Askhatovna; Gabdullin M. T. Maratbek Tulebergenovich; Kadyrzhanov K. K. Kayrat Kamalovich; Nesterov E. A. Evgeny Alexandrovich (2022, 2022)
Title screen